Intracranial Atherosclerotic Stenosis is Related to Post-stroke Cognitive Impairment: A Cross-sectional Study of Minor Stroke - Gong, Li; Wang, Haichao; Dong, Qiong; Zhu, Xiaoping; Zheng, Xiaoran; Gu, Yongzhe; Cai, Wangli; Zhao, Yanxin; Liu, Xueyuan (Current Alzheimer Research, 2020)
Background: Intracranial Atherosclerotic Stenosis (ICAS) is an important risk factor for cognitive impairment. However, it is unclear whether patients with ICAS are more likely to develop cognitive impairment after an acute, non-disabling ischemic stroke (minor stroke). Objective: We aimed to investigate the association between ICAS and post-stroke cognitive impairment. Methods: In this cross-sectional study, patients with acute, non-disabling ischemic stroke underwent two cognitive tests and imaging evaluation for ICAS, within two weeks after the stroke. To determine the association between ICAS and post-stroke cognitive impairment, we performed a multivariate logistic regression analysis adjusted for several demographic and vascular risk factors. Results: Of the 164 patients with minor stroke in this study, 98 (59.76%) were diagnosed with poststroke cognitive impairment (Montreal Cognitive Assessment score<26). After adjusting for potential confounders, we found that patients with ICAS were more likely to develop cognitive impairment after an acute, non-disabling ischemic stroke, compared to patients without ICAS (Odds Ratio: 2.13; 95% Confidence Interval: 1.07-4.26), and underperformed in the tests of visuospatial and executive function. Conclusion: In this cross-sectional study of a population that has experienced a minor stroke, our findings demonstrated a positive association between ICAS and post-stroke cognitive impairment.
Keywords: intracranial stenosis